Assessment of brain mechanisms involved in the processes of thermal sensation, pleasantness/unpleasantness, and evaluation. (June 2019) - Aizawa, Yuka; Harada, Tokiko; Nakata, Hiroki; Tsunakawa, Mizuki; Sadato, Norihiro; Nagashima, Kei
Abstract: The conscious perception of thermal stimuli is divided into two categories: thermal sensation (i.e., discriminative component) and pleasantness/unpleasantness (i.e., hedonic component). There have been very few studies which clearly dissociated the two components. The aim of the present study was 1) to identify brain regions involved in perception of thermal stimuli per se, dissociating those related to the two components, and additionally 2) to examine brain regions of the explicit evaluation processes for the two components. Sixteen participants received local thermal stimuli of either 41.5 °C or 18.0 °C during whole-body thermal stimuli of 47.0 °C, 32.0 °C, or 17.0 °C. The local stimuli were delivered to the right forearm with the Peltier device. The whole-body stimuli delivered through a water-perfusion suit was aimed to modulate thermal pleasantness/unpleasantness to the local stimulus. The local stimulation at the same temperature was conducted five times with 30-s intervals. Brain activation was assessed by functional magnetic resonance imaging (fMRI), and the participants were asked to report their ratings of thermal sensation and pleasantness/unpleasantness following the cessation of each local stimulus. Local thermal stimulation activated specific brain regions such as the anterior cingulate cortex, insula, and inferior parietal lobe, irrespective of the temperature of local and whole-body stimuli; however, no specific activation for hot or cold sensation was observed. Different brain regions were associated with pleasantness and unpleasantness; the caudate nucleus and frontal regions for pleasantness, and the medial frontal and anterior cingulate cortex for unpleasantness. In addition, the explicit evaluation process for the discriminative and hedonic components immediately following the cessation of local stimulus involved different brain regions; the medial prefrontal cortex extending to the anterior cingulate cortex, insula, middle frontal cortex, and parietal lobes during the explicit evaluation of thermal sensation, and the medial prefrontal cortex, posterior cingulate cortex, and inferior parietal lobes during that of pleasantness/unpleasantness.